Aspek-Aspek Yang Mengindikasikan Terjadinya Manajemen Laba - Ni Luh Putu Sandrya Dewi; Ni Putu Dewi Antari (Juara: Jurnal Riset Akuntansi, 2022)
Earnings management is the act of managers choosing accounting policies to achieve certain goals, and the accounting policy in question of accrualism in the preparation of financial statements. How profitability, leverage, financial difficulties and information asymmetry can affect the earnings management of issuers in the banking sector in the 2017-2020 observation year. The sample obtained by the purposive sampling method is 10 companies (40 samples) after 4 years of follow-up, because the other 36 companies' financial statements are inaccessible and do not have receivable data. The analytical method used is multiple linear regression analysis. It is known that all the factors have a positive effect on earnings management.